Video-based multimedia on learners’ attitude towards astrophysics: Gender equity and school location - Gabriel Janvier Tugirinshuti; Leon Rugema Mugabo; Alexis Banuza (Institute of Advanced Engineering and Science, 2022)
Educational literature is richly provided with research confirming the benefits of video-based multimedia (VBM) in education. So, understanding learners’ attitude about learning using video-based multimedia makes sense. A convergent parallel mixed methods research design was used to analyze and interpret learners’ attitudes in the context of learning astrophysics using video-based multimedia. The research involved 294 students (168 male and 126 female) of senior five (grade 11) who purposively selected from eight public secondary schools in Rutsiro and Rubavu districts, Rwanda. Data were collected using a questionnaire (Cronbach alpha=.87), a semi-structured interview, and class observation. Quantitative data were analyzed using descriptive statistics and t-test (P level of significance) while content analysis was employed to analyze qualitative data. The findings revealed that there is no significant difference between male and female attitudes towards the use of video-based multimedia in learning astrophysics. Besides, the geographical location of the school influences the learners’ attitude. The results revealed some factors that affect learners’ attitudes towards learning astrophysics using video-based multimedia. Moreover, the findings recommend how the identified challenges could be alleviated not only in the Rwandan but in other science subjects worldwide.